2021
DOI: 10.48550/arxiv.2111.12849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Particle Graph Autoencoders and Differentiable, Learned Energy Mover's Distance

Abstract: Autoencoders have useful applications in high energy physics in anomaly detection, particularly for jets-collimated showers of particles produced in collisions such as those at the CERN Large Hadron Collider. We explore the use of graph-based autoencoders, which operate on jets in their "particle cloud" representations and can leverage the interdependencies among the particles within a jet, for such tasks. Additionally, we develop a differentiable approximation to the energy mover's distance via a graph neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In a Lund string model the quarks and gluons are thought of being connected by QCD color flux tubes, or strings, that carry significant amounts of energy, and shed it in the process of hadron creation. While there were already attempts to use ML to improve parton shower simulations [27,[65][66][67][68][69][70][71], this manuscript represents the first attempt to use ML for hadronization. In both cases the physics is described by a Markov chain, however, for different reasons.…”
Section: The Simplified Lund String Hadronization Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Lund string model the quarks and gluons are thought of being connected by QCD color flux tubes, or strings, that carry significant amounts of energy, and shed it in the process of hadron creation. While there were already attempts to use ML to improve parton shower simulations [27,[65][66][67][68][69][70][71], this manuscript represents the first attempt to use ML for hadronization. In both cases the physics is described by a Markov chain, however, for different reasons.…”
Section: The Simplified Lund String Hadronization Modelmentioning
confidence: 99%
“…Such ML models could be directly built from data and provide insights into the current phenomenological models. While ML techniques have recently entered into the development of event generators, through adaptive integration [15][16][17][18][19][20], parton showers [21][22][23][24][25][26][27][28][29], ML based fast detector or event simulations , and model parameter tuning [56,57], the application of ML to the problem of hadronization as the final step in the Monte Carlo pipeline is entirely new, to the best of our knowledge. The present manuscript represents the first step toward building a full-fledged ML based hadronization framework.…”
Section: Introductionmentioning
confidence: 99%
“…Recent paradigms emerging in the HEP community, for example anomaly detection methods for model-agnostic physics searches [164], present an exciting opportunity to develop novel graph-based algorithms. To date, several studies have demonstrated the applicability of autoencoders applied to particle graphs for anomaly detection [165,166].…”
Section: New Task Typesmentioning
confidence: 99%
“…5. Additionally, network architectures based on sets or graphs explicitly encoding permutation symmetry of the final state particles have been investigated [39][40][41][42][43][44].…”
Section: Parton Showermentioning
confidence: 99%